Cartilage oligomeric matrix protein responses to a mechanical stimulus associate with ambulatory loading in individuals with anterior cruciate ligament reconstruction. Issue 4 (12th July 2021) - Erhart‐Hledik, Jennifer C.; Titchenal, Matthew R.; Migliore, Eleonora; Asay, Jessica L.; Andriacchi, Thomas P.; Chu, Constance R.
Abstract: Mechanical factors have been implicated in the development of osteoarthritis after anterior cruciate ligament (ACL) reconstruction. This study tested for associations between ambulatory joint loading (total joint moment [TJM] and vertical ground reaction force [vGRF]) and changes in serum levels of cartilage oligomeric matrix protein (COMP) in response to a mechanical stimulus (30‐min walk) in individuals with ACL reconstruction. Twenty‐five subjects (mean age: 34.5 ± 9.8 years; 2.2 ± 0.2 years post‐surgery) with primary unilateral ACL reconstruction underwent gait analysis for assessment of peak vGRF and TJM first (TJM1) and second (TJM2) peaks. Serum COMP concentrations were measured by enzyme‐linked immunosorbent assay immediately before, 3.5 h, and 5.5 h after a 30‐min walk. Pearson correlation coefficients and backward stepwise multiple linear regression analysis, with adjustments for age, sex, body mass index, and between‐limb speed difference, assessed associations between changes in COMP and between‐limb differences in joint loading parameters. Greater TJM1 ( R  = 0.542, p  = 0.005), TJM2 ( R  = 0.460, p  = 0.021), and vGRF ( R  = 0.577, p  = 0.003) in the ACL‐reconstructed limb as compared to the contralateral limb were associated with higher COMP values 3.5 h following the 30‐min walk. Change in COMP at 5.5 h became a significant predictor of the between‐limb difference in TJM1 and vGRF in multivariate analyses after accounting for the between‐limb speed difference. These results demonstrate that higher TJM and vGRF in the ACLR limb as compared to the contralateral limb are associated with higher relative COMP levels 3.5 and 5.5 h after a 30‐min walk. Future work should investigate the effect of therapies to alter joint loading on the biological response in individuals after ACL reconstruction.